Same-sex desire in early modern England, 1550-1735 : an anthology of literary texts and contexts - Loughlin, Marie H., 1962- (Manchester University Press, 2014)
Balancing long-overlooked and well-known works from early modern England, "Same-sex desire in early modern England, 1550-1735: an anthology of literary texts and contexts" is a collection of English texts about homoerotic love, relationships, desires, and sexual acts. The anthology's core texts are selections from works of drama, fiction, romance, poetry, essays and translation. These core texts are carefully introduced and annotated, and supplemented with illuminating contextual material from other early modern disciplines such as law, medicine, and theology. Juxtaposing literary and non-literary representations of same-sex erotic desire, this anthology explores a rich tradition of works both celebrating and condemning same-sex erotic love.